Violações baseadas em gênero perpetradas durante a ditadura no Brasil (1964-1985): uma análise das reparações através do Livro dos Votos - Comissão de Anistia Política - Raquel Cristina Possolo Gonçalves (2021)
When viewed from a feminist perspective, transitional justice can help states in transition to achieve equality between men and women, the foundation of liberal democracy, in a more satisfactory way. Repair programs have been perceived as a good opportunity to reflect on the role of repairs in perpetuating structural inequalities and how they could, on the contrary, contribute to their modifications. This premise is the basis for this work. Starting from this understanding about the reparations, we seek to bring this discussion to the Brazilian context, through the Political Amnesty Commission. Thus, the text that follows is an attempt to answer these questions: was the discussion regarding gender and transitional justice received by the Amnesty Commission? Question that was subdivided into: a) how did the Amnesty Commission deal with gender-based violations?; and, b) Would the Political Amnesty Commission be a good example of a reparations program with regard to gender-sensitive reparations? To this end, twenty-four opinions prepared in response to requests for political amnesty, brought to the Commission for violations against women, were analyzed. The Commission, together with others, adding up to 115 in all, in the Book of Votes, published these opinions in 2014. We highlighted some themes, which received more detailed treatment, given the contribution they brought to the discussion. Thus, these themes were divided into: women and leadership; the invisibility caused by the exaltation of the companion's militancy; forced nudity, threat of rape, torture of companions and electric shocks; maternity or “what do I do to be alive tomorrow?”; women and forced displacement; and, Is a neutral language possible? Neutral language in Law - a tool for maintaining structural inequalities? We conclude with the perception that some of the analyzed opinions contributed to guarantee women's rights, highlighting their leadership, or recognizing their role in their own stories, for example. However, there was also a reaffirmation of stereotypes, invisibilities, and the lack of deeper discussions on gender-based violations.